Marriage Equality: Two Generations of Gender and Sexually Diverse Australians. Issue 103 (2nd January 2020) - Cover, Rob; Rasmussen, Mary Lou; Newman, Christy; Marshall, Daniel; Aggleton, Peter
ABSTRACT: Marriage equality is routinely located as evidencing a domestic, non-radical or neoliberal approach to sexual diversity. This article questions such assumptions by highlighting the reflexive approach to the utility of marriage and the significant diversity of opinion and attitudes towards marriage equality among gender- and sexually-diverse Australians. It does so by drawing on a major study of two social generations of gender- and sexually-diverse Australians' conducted in the lead-up to a controversial postal survey on same-sex marriage in 2017. In the survey many participants discussed their views on marriage equality, its benefits, and how they saw its relationship or relevance to their own lives. This article identifies four themes present in participants' responses: (1) the personal and domestic importance of marriage equality to some participants; (2) the social and political affordances of marriage equality for LGBTQ+ persons in Australia more generally; (3) the apparently unremarkable status of marriage equality for some participants; and (4) continuing deep ambivalence about marriage equality for others.